Solve
(x^2 - 16)(x - 3)^2 + 9x^2 = 0
Here's the partial solution:
(x^2 - 16)(x - 3)^2 + 9x^2 = 0
x^2(x - 3)^2 - 16(x - 3)^2 + 9x^2 = 0
x^2(x^2 - 6x + 9) - 16(x - 3)^2 + 9x^2 = 0
x^4 - 6x^3 + 18x^2 - 16(x - 3)^2 = 0
x^4 - 6x^2(x - 3) - 16(x - 3)^2 = 0
See if you can contniue from there
(x^2 - 16)(x - 3)^2 + 9x^2 = 0
Here's the partial solution:
(x^2 - 16)(x - 3)^2 + 9x^2 = 0
x^2(x - 3)^2 - 16(x - 3)^2 + 9x^2 = 0
x^2(x^2 - 6x + 9) - 16(x - 3)^2 + 9x^2 = 0
x^4 - 6x^3 + 18x^2 - 16(x - 3)^2 = 0
x^4 - 6x^2(x - 3) - 16(x - 3)^2 = 0
See if you can contniue from there